Penularan Fitoplasma Sapu pada Tanaman Kacang Tanah oleh Serangga Vektor Orosius argentatus dan Deteksi Molekuler dengan Teknik PCR - Tatit Sastrini; Kikin Hamzah Mutaqin (Jurnal Fitopatologi Indonesia, 2013)
Witches’ broom disease caused by phytoplasma is a very serious disease on peanut (Arachis hypogaea) which may potentially lead to high yield loss. Insects are the most important agents of phytoplasma transmission in the field. The objective of this research was to examine the potential role of leafhoppers species as insect vector of phytoplasma and to determine their transmission characteristic. Two species of leafhopper i.e. O. argentatus and Empoasca sp. (both belong to Hemiptera: Cicadellidae) were chosen for this study. The methodology involved were transmission study of phytoplasma by O. argentatus and Empoasca sp., and molecular detection of phytoplasma by PCR technique to confirm the association of pathogen, insect vector and symptomatic plants. The result showed that specific symptom was observed when using O. argentatus in the transmission study with number of insect as low as 1 insect per plant, whereas Empoasca sp. was not able to transmit the disease. Incubation period of phytoplasma in the host plant was affected by the number of insect, i.e. the more insect vector the shortest incubation period. The phytoplasma was successfully detected using P1/P7 primer in symptomatic plants as well as in the insect vector.Key words: Empoasca sp., leafhoppers, polymerase chain reaction